2018
DOI: 10.1074/mcp.ra117.000393
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Succinylation Contributes to Aflatoxin Production and Pathogenicity in Aspergillus flavus

Abstract: Aspergillus flavus (A. flavus) is a ubiquitous saprophytic and pathogenic fungus that produces the aflatoxin carcinogen, and A. flavus can have tremendous economic and health impacts worldwide. Increasing evidence demonstrates that lysine succinylation plays an important regulatory role in metabolic processes in both bacterial and human cells. However, little is known about the extent and function of lysine succinylation in A. flavus. Here, we performed a global succinylome analysis of A. flavus using high acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 85 publications
1
66
0
Order By: Relevance
“…In A. flavus , Lan found that histone acetyltransferase and deacetylase play important roles in the production of aflatoxin by regulating modifications of histone acetylation (Lan et al ., ; Lan et al ., ). In addition, the results of acetylation‐mediated aflatoxin biosynthesis agree with the results of other reported PTMs in A. flavus , including phosphorylation (Ren et al ., ), SUMOylation (Nie et al ., ) and succinylation (Ren et al ., ). Taken together, we conclude that lysine acetylation is critical for secondary metabolism in A. flavus .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In A. flavus , Lan found that histone acetyltransferase and deacetylase play important roles in the production of aflatoxin by regulating modifications of histone acetylation (Lan et al ., ; Lan et al ., ). In addition, the results of acetylation‐mediated aflatoxin biosynthesis agree with the results of other reported PTMs in A. flavus , including phosphorylation (Ren et al ., ), SUMOylation (Nie et al ., ) and succinylation (Ren et al ., ). Taken together, we conclude that lysine acetylation is critical for secondary metabolism in A. flavus .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that histone deacetylase‐mediated acetylation modification regulates development, aflatoxin biosynthesis and pathogenicity of A. flavus (Lan et al ., ). In addition, proteomics analysis of phosphorylation and succinylation indicated that phosphorylation and succinylation regulate the development, pathogenicity and aflatoxin biosynthesis of A. flavus by regulating the function of key proteins (Ren et al ., ; ). Therefore, we believe that acetylation plays an important role in regulating various processes, and the model is suitable for the results presented in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of Lysine-succinylated Peptides-To enrich for a high abundance of lysine-succinylated peptides, immunoaffinity analysis was performed using agarose-conjugated anti-succinyllysine antibody (PTM Biolabs Inc., Hangzhou, China), as previously described (27). Briefly, the tryptic digested peptides were incubated with antisuccinyllysine agarose beads overnight at 4°C in NETN buffer (100 mM NaCl, 50 mM Tris-HCl, 1 mM EDTA, and 0.5% Nonidet P-40, pH 8.0), and then eluted with 1% trifluoroacetic acid (TFA).…”
Section: Methodsmentioning
confidence: 99%
“…It should, however, be noted that the succinylation proteins overlap with other modifications due to some exhibiting dual properties. Recently many studies have suggested that lysine succinylation extensively overlaps with acetylation [25,27,42,63,68,73,74,75,76].…”
Section: Existing Prediction Modelsmentioning
confidence: 99%
“…This modification can make notable alterations in protein function and structure regulation [3,13,35,36,37]. It can also participate in regulating many biological processes such as calorie restriction and metabolisms [38,39,40,41,42,43,44]. The identification of protein succinylation sites is a crucial topic in cellular pathology and physiology, which may provide valuable information for biomedical research and drug development.…”
Section: Introductionmentioning
confidence: 99%